Development of augmented reality media based on Assemblr Edu to enhance the learning outcomes - La Shita Ardia Damayanti; Galih Mahardika Christian Putra (Research and Development in Education)
This study focuses on the development and evaluation of augmented reality (AR) learning media based on the Assemblr Edu application, aimed at enhancing the learning experience of fifth-grade students at SDN Tambaharjo 01. The AR media covers the subject of Community Economic Conditions and Natural Resources and Supporting Factors for Community Economic Activities. The research process included designing the AR content, validating it with experts, and conducting small and large group trials. This study investigates the development and effectiveness of AR learning media based on the Assemblr Edu application to improve learning outcomes in Natural Science and Social Studies for fifth-grade students at SD Negeri Tambaharjo 01. The research employs a quantitative approach with a Research and Development (R&D) method, utilizing the ADDIE development model to create and assess the learning media. The study addresses low student performance in Natural Science and Social Studies by integrating interactive AR technology to make learning more engaging and effective.The developed AR media, which includes 3D and 2D interactive content, was validated by material and media experts, yielding a high validity score of 90.31%. Small and large group trials were conducted, showing significant improvements in student learning outcomes. Pretest and posttest results demonstrated an average score increase from 50 to 85, with a student response rate of 88.46% indicating the media's feasibility. Teachers also rated the AR media highly, with a response score of 91.34%, confirming its practical application in educational settings. The study concludes that the Assemblr Edu-based AR learning media is highly feasible and effective in enhancing student learning outcomes in Natural Science and Social Studies.